Leisure time physical activity and dementia risk: a dose-response meta-analysis of prospective studies. Issue 10 (22nd October 2017) - Xu, Wei; Wang, Hui Fu; Wan, Yu; Tan, Chen-Chen; Yu, Jin-Tai; Tan, Lan
Abstract : Background: There is considerable evidence of the favourable role of more physical activity (PA) in fighting against dementia. However, the shape of the dose–response relationship is still unclear. Objective: To quantitatively investigate the relationship between dementia and PA. Design: PubMed, EMBASE, Ovid and the Cochrane Library were searched for prospective studies published from 1 January 1995 to 15 October 2016. Two types of meta-analyses were performed with a focus on the dose–response relationship using two stage generalised least squares regression. Results: The primary analysis exhibited a dose–response trend for all-cause dementia (ACD), Alzheimer's disease (AD) but not for vascular dementia (VD). In the dose–response analysis, either ACD (ptrend <0.005; pnon-linearity =0.87) or AD (p trend <0.005; pnon-linearity =0.10) exhibited a linear relationship with leisure time PA (LTPA) over the observed range (0–2000 kcal/week or 0–45 metabolic equivalent of task hours per week (MET-h/week)). Specifically, for every 500 kcal or 10 MET-h increase per week, there was, on average, 10% and 13% decrease in the risk of ACD and AD, respectively. Conclusions: We have reported, for the first time, the dose–response relationship between LTPA and dementia, further supporting the international PA guideline from the standpoint of dementia prevention.